Non-profits and the 'hollowed out' state: the transformation of working conditions through personalizing social care services during an era of austerity. (August 2016) - Cunningham, Ian
This article explores the impact of state reforms to increase customer authority in social care at a time of public sector austerity in Scotland. The article focuses on the implications of these reforms for state–non-profit relations and the latter's employment policies. The study proposes a theoretical framework to explore these themes using insights from the 'hollowing out' thesis and the customer-orientated bureaucracy concept. Non-profits respond to increased customer authority from personalization and public expenditure cuts by adopting more competitive relations with each other. They also introduce contradictory 'soft' and 'hard' Human Resource Management (HRM) reforms. Workers face multiple demands to be more flexible and exhibit commitment to 'fit' with customer needs. Despite some increases in skills, the increasing influence of customer authority and efficiency savings mean employees experience multiple degradations in employment conditions affecting pay, job security, skills and work intensification.